Performance Assessment of Development West Halmahera Forest Management Unit, of North Mollucas Province - Taher , Iswan; Niapele, Sabaria; Salim, Tamrin; Husen, Sadam S.; Julham, Muhammad; Putri, Wiwin Failysa (Agrikan Jurnal Agribisnis Perikanan, 2025)
This study aims to analyze the management performance of the Sasadu Bidadari Production Forest Management Unit of West Halmahera using the assessment guidelines for Forest Watch Indonesia (FWI) criteria and indicators version 2.0. The number of respondents collected consisted of 5 respondents, namely the Head of FMU West Halmahera, Head of Forest Planning and Utilization Section of FMU West Halmahera, Head of KSDAE Protection and Community Empowerment Section of FMU West Halmahera. Head of the Forest Area Planning and Utilization Division of the North Maluku Province Forestry Service, and Head of BPKH Region VI Manado. The data collected was then processed using Forest Watch Indonesia (FWI) Criteria and Indicators version 2.0. The final result of this analysis is presented in the form of an index. The results show that the assessment of Forest Watch Indonesia (FWI) version 2.0 criteria and indicators, which have been modified based on applicable regulations, places the development management performance of the West Halmahera FMU in the high category with an index value of 2.51. Based on the assessment results, there are three criteria in the medium category, namely the forest governance criteria, investment mechanism, and conflict handling. Meanwhile, six criteria are in the high category, namely the criteria for area stability, management plan, organizational capacity, government and regulatory relations, rights and access mechanism for the community, and management implementation within the FMU scope.